2000
DOI: 10.1161/01.hyp.35.5.1069
|View full text |Cite
|
Sign up to set email alerts
|

Proapoptotic and Growth-Inhibitory Role of Angiotensin II Type 2 Receptor in Vascular Smooth Muscle Cells of Spontaneously Hypertensive Rats In Vivo

Abstract: Abstract-Angiotensin type 2 (AT 2 ) receptors for angiotensin II suppress cell growth and induce apoptosis in vitro, but their role is poorly defined in vivo. We reported that transient induction of smooth muscle cell (SMC) apoptosis precedes DNA synthesis inhibition and aortic hypertrophy regression in spontaneously hypertensive rats treated with the AT 1 antagonist losartan or the converting-enzyme inhibitor enalapril. Although both drugs are equipotent in reducing SMC number, apoptosis occurs significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
70
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(76 citation statements)
references
References 52 publications
6
70
0
Order By: Relevance
“…Although we did not measure Ang II levels in the rats treated with candesartan cilexetil, it would be expected that this treatment would have elevated Ang II levels at least 5-fold. 34 As expected, candesartan cilexetil virtually abolished Ang II-evoked contraction in mesenteric arteries, which is consistent with the prolonged duration of action of this compound, both in vivo 25 and ex vivo. 24 Although it was not expected that AT 1 R blockade would directly affect AT 2 Rmediated responses (because different receptor subtypes), it was not known if increased circulating levels of Ang II could desensitize the action of Ang II at AT 2 Rs, as occurred at AT 1 Rs.…”
supporting
confidence: 84%
“…Although we did not measure Ang II levels in the rats treated with candesartan cilexetil, it would be expected that this treatment would have elevated Ang II levels at least 5-fold. 34 As expected, candesartan cilexetil virtually abolished Ang II-evoked contraction in mesenteric arteries, which is consistent with the prolonged duration of action of this compound, both in vivo 25 and ex vivo. 24 Although it was not expected that AT 1 R blockade would directly affect AT 2 Rmediated responses (because different receptor subtypes), it was not known if increased circulating levels of Ang II could desensitize the action of Ang II at AT 2 Rs, as occurred at AT 1 Rs.…”
supporting
confidence: 84%
“…However, an imbalance between growth and apoptosis could be important (128,190). Many studies (27,151,166) have suggested that ACE inhibitors and AT 1 R blockers could contribute to regression of vascular wall growth through activation of proapoptotic pathways. Apoptosis may also play a role in microvascular rarefaction, which has been implicated in the development of hypertension (56).…”
Section: Role Of Ang II In Vascular Structural Changes In Hypertensionmentioning
confidence: 99%
“…Most well-known effects of Ang II that contribute to unfavorable vascular remodeling and consequent hypertensive complications are mediated via AT 1 R, whereas those exerted via AT 2 R are less well known and appear to counteract many of its effects exerted via AT 1 R. 4,5 AT 2 Rmediated effects seem to exert vasculoprotective actions via vasodilation, NO production, 6 -8 and apoptosis and inhibition of growth and fibrosis. 5,9,10 Beneficial vascular effects of AT 1 R blockade have been at least partially attributed to unopposed AT 2 R stimulation. 7,11,12 …”
mentioning
confidence: 99%
“…Most well-known effects of Ang II that contribute to unfavorable vascular remodeling and consequent hypertensive complications are mediated via AT 1 R, whereas those exerted via AT 2 R are less well known and appear to counteract many of its effects exerted via AT 1 R. 4,5 AT 2 Rmediated effects seem to exert vasculoprotective actions via vasodilation, NO production, 6 -8 and apoptosis and inhibition of growth and fibrosis. 5,9,10 Beneficial vascular effects of AT 1 R blockade have been at least partially attributed to unopposed AT 2 R stimulation. 7,11,12 Several studies have suggested beneficial vascular effects of AT 2 R. We reported previously that AT 2 R mediated downregulation of vascular RhoA/Rho kinase/myosin light chain phosphorylation in Ang II and AT 1 R antagonist valsartantreated or AT 2 R partial agonist CGP42112A-treated cultured vascular smooth muscle cells, suggesting a role for vascular AT 2 R in blood pressure (BP) lowering during chronic AT 1 R blockade.…”
mentioning
confidence: 99%